A Porous Cobalt Tetraphosphonate Metal–Organic Framework: Accurate Structure and Guest Molecule Location Determined by Continuous‐Rotation Electron Diffraction. Issue 66 (30th October 2018) - Wang, Bin; Rhauderwiek, Timo; Inge, A. Ken; Xu, Hongyi; Yang, Taimin; Huang, Zhehao; Stock, Norbert; Zou, Xiaodong
Abstract: Single‐crystal electron diffraction has shown to be powerful for structure determination of nano‐ and submicron‐sized crystals that are too small to be studied by single‐crystal X‐ray diffraction. However, it has been very challenging to obtain high quality electron diffraction data from beam sensitive crystals such as metal–organic frameworks (MOFs). It is even more difficult to locate guest species in the pores of MOF crystals. Here, we present synthesis of a novel porous cobalt MOF with 1D channels, [Co2 (Ni‐H4 TPPP)]⋅2 DABCO⋅6 H2 O, (denoted Co‐CAU‐36; DABCO=1, 4‐diazabicyclo[2.2.2]octane), and its structure determination using continuous rotation electron diffraction (cRED) data. By combining a fast hybrid electron detector with low sample temperature (96 K), high resolution (0.83–1.00 Å) cRED data could be obtained from eight Co‐CAU‐36 crystals. Independent structure determinations were conducted using each of the eight cRED datasets. We show that all atoms in the MOF framework could be located. More importantly, we demonstrate for the first time that organic molecules in the pores, which were previously difficult to find, could be located using the cRED data. A comparison of eight independent structure determinations using different datasets shows that structural models differ only on average by 0.03(2) Å for the framework atoms and 0.10(6) and 0.16(12) Å for DABCO and water molecules, respectively. Abstract : Continuous‐rotation electron diffraction (cRED) was used as a stand‐alone method for both structure solution and refinement of submicron‐sized crystals of a novel cobalt metal–organic framework. We show that the method is robust; not only the framework structure, but also solvent molecules in the pores could be precisely located.